PENYELESAIAN TINDAK PIDANA PENGGANIAYAAN SECARA MEDIASI PENAL BERDASARKAN HUKUM ADAT PADA MASYARAKAT DESA KECAMATAN KABUN KABUPATEN ROKAN HULU - Fajri, Muhammad Al; Deliana, Evi; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
This study examines the settlement of criminal acts of torture by mediating the penaltieswhich were resolved through the Kabun District adat institutions so that they can be resolvedpeacefully as quickly as possible. The problem under study is How is the resolution of thecriminal act of torture mediated by penalties based on customary law in the village communityof Kabun District, Rokan Hulu Regency? as well as inhibiting factors in the resolution ofcriminal acts of torture by mediating penalties based on customary law in the villagecommunity of Kabun District, Rokan Hulu Regency?This study uses normative and empirical juridical approaches. The data used includeprimary data and secondary data. The data collection method in this research is to useliterature study and field study. The data processing is carried out by means of Editing thendata classification, Interprestion and data systematization are carried out. Data analysis wasperformed in a qualitative manner.The results of research and discussion show that the process of resolving cases ofcriminal acts of persecution using the mediation of penalties consists of the stages of themeeting consisting of the initial opening, delivery of problems between the parties,identification of agreed matters, formulation and preparation of the negotiation agenda,discussion of issues, laughter - Bidding on case resolution, decision making, and closingstatement. While the post-mediation stage consists of ratification of the results of theagreement, sanctions, obligations of the actors signing the peace agreement. Mediation wascarried out by previously making several considerations, among others, the victim agreed tohold a peaceful effort and resolved through family ties, the impact if the case continues, it isfeared that it will cause a trauma to both the perpetrator and his familyThe implication of this research is that the government needs to make laws andlimitations for criminal acts that can be resolved through mediation at the Customary level, thePolice and the Government need to make laws regarding the procedures for implementingmediation of penalties so that the practice of applying them in the field puts forward thedeliberation approach can be realized in the customary law of the Kabun sub-district.Keyword: Penal Mediation - Criminal Acts of Abuse - Customary Institution